Psychosis in autism: Comparison of the features of both conditions in a dually affected cohort. (April 2017) - Larson, Felicity V.; Wagner, Adam P.; Jones, Peter B.; Tantam, Digby; Lai, Meng-Chuan; Baron-Cohen, Simon; Holland, Anthony J.
Abstract : Background: There is limited information on the presentation and characteristics of psychotic illness experienced by people with autism spectrum disorder (ASD). Aims: To describe autistic and psychotic phenomenology in a group of individuals with comorbid ASD and psychosis (ASD–P) and compare this group with populations affected by either, alone. Method: We studied 116 individuals with ASD–P. We compared features of their ASD with people with ASD and no comorbid psychosis (ASD–NP), and clinical characteristics of psychosis in ASD–P with people with psychosis only. Results: Individuals with ASD–P had more diagnoses of atypical psychosis and fewer of schizophrenia compared with individuals with psychosis only. People with ASD–P had fewer stereotyped interests/behaviours compared with those with ASD–NP. Conclusions: Our data show there may be a specific subtype of ASD linked to comorbid psychosis. The results support findings that psychosis in people with ASD is often atypical, particularly regarding affective disturbance.